HOW WORKFLOW OPTIMIZATION IMPROVES PATIENT CARE - Ramesh Pingili, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This study examines how workflow optimization systems transform healthcare delivery through advanced technologies and AI integration. Research across multiple healthcare facilities demonstrates significant improvements: a 45% reduction in documentation time, 37.8% decrease in critical care response times, and average cost savings of $428 per patient encounter. Implementation of these systems, while challenging, shows consistent benefits: 42.8% reduction in scheduling conflicts, 47.2% decrease in hospital readmission rates, and 41.3% reduction in equipment downtime. The findings provide a roadmap for healthcare organizations transitioning to optimized, patient-centered care delivery models.